1999
DOI: 10.2337/diabetes.48.8.1535
|View full text |Cite
|
Sign up to set email alerts
|

Glucose regulation of glutaminolysis and its role in insulin secretion.

Abstract: Leucine or the nonmetabolized leucine analog +/- 2-amino-2-norbornane-carboxylic acid (BCH) (both at 10 mmol/l) induced biphasic insulin secretion in the presence of 2 mmol/l glutamine (Q2) in cultured mouse islets pretreated for 40 min without glucose but with Q2 present. The beta-cell response consisted of an initial peak of 20- to 25-fold above basal and a less marked secondary phase. However, BCH produced only a delayed response, while leucine was totally ineffective when islets were pretreated with 25 mmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
105
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 14 publications
10
105
1
1
Order By: Relevance
“…Therefore, islet glutamate levels can be markedly increased by exposure to extracellular glutamine and, because of scarce conversion of glutamate to α-ketoglutarate [24], without stimulation of insulin secretion [24,55]. Activation of GDH by L-leucine or its non-metabolisable analogue BCH increases glutamine oxidation and insulin secretion, essentially by enhancing the oxidative deamination of glutamate [25,27,28,29,32,33,56]. GDH activity is under the tight control of allosteric effectors, although the flux direction depends chiefly on the relative supply of substrates and cofactors, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, islet glutamate levels can be markedly increased by exposure to extracellular glutamine and, because of scarce conversion of glutamate to α-ketoglutarate [24], without stimulation of insulin secretion [24,55]. Activation of GDH by L-leucine or its non-metabolisable analogue BCH increases glutamine oxidation and insulin secretion, essentially by enhancing the oxidative deamination of glutamate [25,27,28,29,32,33,56]. GDH activity is under the tight control of allosteric effectors, although the flux direction depends chiefly on the relative supply of substrates and cofactors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…glutamate, α-ketoglutarate, and NAD(P) + /H respectively. Accordingly, glutamine oxidation stimulated by the presence of an allosteric activator of GDH is inhibited by glucose [28], which increases the carbon pool on the TCA cycle side. The glutamate and α-ke toglutarate pathway is operated either by GDH or alternatively by transamination reactions [57,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, it has been shown that insulin secretion can be stimulated by leucine, which activates GDH. 20 The differential diagnosis of infantile nonketotic hypoglycemia has been extended. It is now clear that in every case of suspected hyperinsulinism blood ammonia levels should be determined, preferably together with plasma amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine has been reported to enhance glucose-or leucine-stimulated insulin secretion from pancreatic ß-cells (located in the endocrine islets of Langerhans), but does not promote insulin secretion by itself due to tight regulation of glutamate dehydrogenase activity (56,57). Glutamine may act as an anaplerotic substrate in the ß-cell, via formation of glutamate and 2-oxoglutarate, subsequently stimulating a catalytic enhancement of glucose oxidation (58).…”
Section: Glutamine/glutamate In the Pancreatic ß-Cellmentioning
confidence: 99%